Racial and Gender Wage Differentials in South Africa: What can Cohort Data tell? - Carola Grün (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2003)
Three subsequent years of the October Household Survey data are used to construct a synthetic panel. Preparing cross sectional data that way allows to better utilise individual information and to address temporal developments also in the absence of genuine panel data. This paper focuses on gender and race specific cohort wages. Average earnings of birth cohorts of African and White workers employed full-time in formal sector jobs are followed over time and wage differentials as well as the mobility of cohort wages are studied in detail. A decomposition of African cohort wages into age, cohort, and year effects gives information about the existence of cohort effects. Results suggest that especially for African women such generational trends may differ from the theoretical expectation. However, to arrive at assured results a greater number of periods is needed.
urn:nbn:de:bvb:19-epub-85-6
Keywords: D31; J31; 330; Cohort data; Gender and racial wage differentials; Generational trends